Green Marketing and Brand Image: Strengthen Consumers’ Purchase Decisions Through Brand Trust on Mineral Water Aqua Consumers in Pekanbaru City - Lisa Melinda; Sri Restuti; Jushermi Jushermi (Westscience Press, 2024)
This study aims to find out the effect of Green Marketing and Brand Image on the purchase decisions of Mineral Water AQUA consumers in Pekanbaru City through the moderation of Brand Trust. The population in this study is the residents of Pekanbaru who purchase and consume AQUA Mineral Water. Sampling was done using purposive sampling technique with a total of 226 respondents. Data analysis used was SMART PLS 3.2.9. The results research: 1) Green Marketing has a positive and significant effect on the Brand Trust of AQUA Mineral Water consumers in Pekanbaru City. 2) Brand Image has positive and significant effect on the Brand Trust of AQUA Mineral Water consumers in Pekanbaru City. 3) Green Marketing has a positive and significant effect on Purchase Decisions 4) Brand Image has positive effect on Purchase Decisions is positive but insignificant. 5) Green Marketing has a positive and significant effect on Purchase Decisions through Brand Trust as a moderating variable for AQUA Mineral Water consumers in Pekanbaru City. 6) Brand Image has a positive and significant influence on Purchase Decisions through Brand Trust as a moderating variable on AQUA Mineral Water consumers in Pekanbaru City. 7) Brand Trust has positive and significant impact on the Purchase Decisions on AQUA Mineral Water consumers in Pekanbaru City.